Does Supplemental Instruction Support the Transition From Spanish to English Reading Instruction for First-Grade English Learners at Risk of Reading Difficulties?. (November 2016) - Baker, Doris Luft; Burns, Darci; Kame'enui, Edward J.; Smolkowski, Keith; Baker, Scott King
This study examines the effect of 30 min of small group explicit instruction on reading outcomes for first-grade Spanish-speaking English learners (ELs) at risk of reading difficulties. Participants were 78 ELs from seven schools who were receiving Spanish only, or Spanish and English, whole group reading instruction in first grade. Students were rank-ordered within schools and then randomly assigned to a treatment condition ( n = 39) or a comparison condition ( n = 39). Students in the treatment condition received instruction on transition elements that supported their transfer of skills from Spanish to English. Students in the comparison condition received Business as Usual instruction from a variety of commercially available programs. Findings indicated that ELs in both conditions made significant gains from pretest to posttest on all reading outcomes even though instruction in the treatment condition focused significantly more on higher order skills (i.e., vocabulary, comprehension, and transition elements) whereas instruction in the comparison condition focused significantly more on lower order skills (i.e., phonics, word work, and sentence reading). Implications for practice and future research are discussed.